CLINICAL AND EPIDEMIOLOGICAL FEATURES OF HERPES ZOSTER IN KHORAZM (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
Herpes zoster (HZ) is one of the common viral skin disease with typical clinical picture and well known etiology and pathogenesis. Epidemiological and clinical peculiarities and differences of herpes zoster in different ethnic groups and geographical regions still present a field of special interest.